GLOBAL PLATFORMS, LOCAL MARKETS: THE PLATFORMIZATION OF MEDIA AND PUBLISHING IN THE PHILIPPINES - Parnell, Claire (AoIR Selected Papers of Internet Research, 2023)
The cultural industries have transformed due to processes of platformization (Poell et al., 2021). This paper examines the platformization of media and publishing in the Philippines, using Wattpad a case study. Wattpad has embedded itself in the Filipino media and publishing industries by developing partnerships with book publishers and television studios, and is transforming and adapting the local media industries. What opportunities exist for decolonization of media content in the platformization of the cultural industries in the Philippines? What are the conditions of the Filipino media landscape that contribute to the success of Wattpad’s pan-entertainment strategy in this territory? This paper brings together publishing studies, platform studies and media ecology and draws on interviews with Wattpad authors in the Philippines. It argues that post-colonial tensions play out in the dominant languages of traditional and platformed cultural production, Wattpad is creating opportunities for greater diversity and inclusion in Filipino book and media culture, and media products developed from Wattpad benefit from distinctly Filipino modes of reception.